2018
DOI: 10.31285/agro.22.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Estructura de las comunidades herbáceas en áreas con plantaciones forestales

Abstract: Este trabajo tuvo como objetivo caracterizar la composición específica, la riqueza, equidad y diversidad de comunidades de sotobosque, callejones cortafuego y campo natural. El estudio se realizó en tres localidades, en 18 transectas con direcciones N-S y E-O ubicadas en la entrefila, callejones cortafuego y campo natural, localizando 30 marcos de 0,25 m 2 en cada una. Fueron relevadas 172 especies clasificadas por familia y género, y se calculó para la vegetación de cada sitio la riqueza, equidad y diversidad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Also, species richness was lower in the region under the canopy in both Brunisol situations, while no differences were detected in the Solonetz. Silveira et al (2018) found that the highest values in the number of families, genera, and plant species were associated with more luminous environments and that the vegetation developed in more illuminated environments presented higher values of richness and diversity.The C3 grass species which had highest soil cover under the tree canopy (total shade) included Bromus catharticus Vahl, Lolium multi orum, Stipa hialina, and S. setigera (Table 5). The C4 grass species wich had lowest soil cover under the canopy, included Bouteloua megapotamica (Spreng.)…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Also, species richness was lower in the region under the canopy in both Brunisol situations, while no differences were detected in the Solonetz. Silveira et al (2018) found that the highest values in the number of families, genera, and plant species were associated with more luminous environments and that the vegetation developed in more illuminated environments presented higher values of richness and diversity.The C3 grass species which had highest soil cover under the tree canopy (total shade) included Bromus catharticus Vahl, Lolium multi orum, Stipa hialina, and S. setigera (Table 5). The C4 grass species wich had lowest soil cover under the canopy, included Bouteloua megapotamica (Spreng.)…”
Section: Resultsmentioning
confidence: 90%
“…Although some studies have studied silvopastoral systems in Uruguay (Bussoni et al 2019;Bernardi et al 2016;Fedrigo et al 2018a;Silveira et al 2018;2022;2023), there is limited information on the systematic effect of trees on the species and functional composition of native grasslands. Thus, this research aimed i) to detect gradients in the botanical composition of native grasslands associated with the effect of the shade by existent trees of the natural forest in Uruguay, and ii) to characterize the species of the native grasslands by their behavior under different projections of light and shade.…”
Section: Introductionmentioning
confidence: 99%
“…En cada cuadro se determinó en porcentaje la cobertura vegetal (CV), mantillo + heces (M+H), restos secos (RS) y suelo descubierto (SD). La cobertura vegetal (CV) correspondió a la suma de las coberturas relativas de cada una de las especies (Braun, 1950;Silveira et al, 2018). Se realizó la clasificación de las especies relevadas en siete TFP: gramíneas perennes invernales (GPI), gramíneas perennes estivales (GPE), gramíneas anuales invernales (GAI), leguminosas (Leg), malezas de campo sucio (MCS, grupo integrado por especies subarbustivas y espinosas), Ciperáceas, Juncáceas y Liliáceas (Cyp -Jun -Lil) y especies de hierbas menores (HM).…”
Section: Variables Evaluadasunclassified
“…La intensidad de luz incidente, la calidad de la luz, el balance de radiación y condiciones hídricas sobre el estrato herbáceo puede modificar la composición botánica, la relación C 4 /C 3 (Pillar et al, 2002;Carvalho et al, 2002;Silveira et al, 2018;2022).…”
Section: Introductionunclassified